Conflitos sócio-ambientais urbanos : o lugar como categoria de análise da produção de Curitiba/Jardim Icaraí - Lima, Rosirene Martins (2007)
Orientadores: Olga Lúcia C.de F.Firkowski, Francisco Mendonça e Eleusis Ronconi